INOVASI PERANCANGAN ENTERPRISE RESOURCE PLANNING (ERP) DALAM MENDUKUNG KINERJA PERUSAHAAN MAKANAN - Yuwono, Wisnu; Imas, Latifa Al Rosyidah; Yingfanie, Melissa; Nuraini, Sharfina Intan; Suheri, Falda; Ginting, Dinda Tri Ninta; Putra, Christian Hadinatan (Indo-Fintech Intellectuals: Journal of Economics and Business, 2025)
Company A, engaged in the food and beverage industry, faced challenges in supply chain management due to the inefficient implementation of its Enterprise Resource Planning (ERP) and Supply Chain Management (SCM) systems. The increasing market demand necessitated the integration of these technologies to improve operational efficiency, ensure timely availability of raw materials and product distribution while improving overall competitiveness. This study aims to analyze the effectiveness of ERP systems in optimizing operational efficiency through productive integration with SCM, focusing on workflow optimization and data accuracy across the supply chain. This study uses a descriptive qualitative approach drawn from secondary sources to understand the relationship between ERP, SCM, and operational performance. The results show that the implementation of ERP and SCM has not been optimized due to lack of training, weak managerial support, and technical constraints such as infrastructure and legacy system integration. This study recommends a comprehensive change management approach, continuous role-based training, and regular system monitoring to reduce downtime. By implementing these strategies, the company can sustainably improve supply chain efficiency and competitiveness.